PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH (PBL) TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII SMP PELAJARAN 2014/2015 - Yandi, Fitra (Jurnal Ilmiah Mahasiswa FKIP Prodi Matematika, 2016)
The purpose of this study was to know whether there was effect of learning model problem based learning through mathematics studentsâ motivation of grade VIII student junior high school 1 Ujungbatu in academic year 2014/2015. The type of this research was pre-experimental research by research design that used one group pretest- posttest design. The population in this research were students class VIII SMP Negeri 1 which was consist of the eighth class. The selection sample on this research was by purposive sampling technique, elected class VIII 1. The instrument of this research was studentsâ motivation questionnaire that had been validated. For analyzing questionnaire data, the research used the sign test and Wilcoxon signed rank test. From the result of analysis data could be concluded that the effect of learning model problem based learning (PBL) through studentsâ mathematics motivation class VIII SMP Negeri 1 Ujungbatu in academic year 2014/2015.